Anatomical Study of the Accessory Genital Glands in Males Sheep (Ovis aris) and Goats (Caprus hircus): Azhar S. Khalaf ,Shaker M. Merhish - Khalaf, Azhar S. (The Iraqi Journal of Veterinary Medicine, 2010)
The study revealed that the ampullae of ductus deferens(vas deferens), seminal vesicle and bulbourethral glands are paired in number and well developed in ram and buck except the prostate gland have only disseminated part surrounding the pelvic urethra (embedded in pelvic urethral wall) without body of gland. The anatomical parameters of the ampullae in ram are generally with mean length 4.98± 0.28cm,mean width 0.63 ± 0.04cm ,mean weight 2.24 ± 0.007gms and mean volume 1.4±0.03cm3.The seminal vesicle have mean length 3.68± 0.05cm, mean width 2.50±0.06cm ,mean weight 4.42± 0.15gms , mean volume 3.35±0.05cm3 .The bulbourethral gland have mean length 1.59± 0.36cm ,mean width 1.493±0.02cm ,mean weight 3.46±0.01gms ,mean volume 2.35±0.04cm3. The anatomical parameters of the ampullae in buck have mean length 4.87±0.29cm ,mean width 0.62±0.007cm, mean weight 2.18±0.007gms , mean volume 1.15±0.02cm3. the seminal vesicle gland parameters have mean length 3.61±0.01cm ,mean width 2.44±0.01cm, mean weight 4.18±0.15gms mean volume 3.05±0.04cm3.The bulbourethral gland parameters have mean length 1.58±0.005cm, mean width 1.46±0.006cm , mean weight 3.23±0.11gms and mean volume 2.05±0.03cm3.Generally the study did not observe any anatomical differences between the male accessory genital glands of ram and buck.